Uso da Pistia stratiotes como fitorremediadora de recursos hídricos contaminados por clomazone - Escoto, Dandara Fidélis (2017)
With the growth of world population and the advent of industrialization, the demand for abundant and profitable food production worldwide is increasing. There is then a need for strategies that minimize loss and changes in food products, especially those that are grown for long periods of time like grains and vegetables. In this bias arise the pesticides, marketed since the nineteenth century, increasingly specialized and chemically modified to achieve greater efficiency in pest elimination and a shorter period of time. When pesticides are used correctly, they minimize grain losses by over 40%, but when used improperly or above the recommended dosage, they can lead to environmental and public health impacts. In this context, Clomazone (2 - (2-chlorobenzyl) -4,4-dimethyl-1,2-oxazolidin-3-one), active principle of the commercial herbicide Gamit®, of the Isoxazolidinone family and belonging to toxicological class III is Of broad spectrum used for the control of annual grasses and broadleaf weeds in cotton, peas, squash, soybeans, sweet potatoes, tobacco, wheat and rice. However, this herbicide has a series of physico-chemical characteristics and distinct behavior depending on the environment where it is inserted which can cause the increase of its permanence in the environment and contamination of organisms that are not its origin targets. An alternative to reduce the environmental impact caused by herbicides is phytoremediation. Phytoremediation consists of a technique of removal and / or pollutants from environments using plants as environmental remediation agents. This study aimed to evaluate the ability of the Pistia Stratiotes plant species in phytoremediation of the herbicide clomazone in its commercial form of water resources. The assay lasted 24 days and counted on two herbicidal concentrations that were determined from the one hundred fold multiplication of the dose recommended for use in crops, setting up an acute exposure to the herbicide. The clomazone degradation kinetics analyzes were performed by analytical methods by high performance liquid chromatography coupled to a detector with CLAE-DAD diode array. After 24 days of experiment, it was possible to identify that the plant species was able to reduce the presence of the herbicide clomazone in water by 90% and also that despite the water exposure to P. stratiotes does not undergo morphological changes due to sensitivity to the compound. Thus, the results indicate that Pistia Straiotes is capable of phytoremediation of the herbicide clomazone of water resources.